2020
DOI: 10.1590/1519-6984.216820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of sugarcane molasses as a carbon source for Ankistrodesmus gracilis and Haematococcus pluvialis (Chlorophyceae)

Abstract: Two species of Chlorophyceae, Ankistrodesmus gracilis and Haemotococcus pluvialis, were used to compare and evaluate the effect of sugarcane molasses as a carbon source. Highest cell density in the two microalgae culture media was obtained in commercial culture media (CHU12 and WC). During exponential growth (day 1 to day 10), high cell density in H. pluvialis was detected for E. crassipes culture medium ranging between 0.4 x 105 cells mL-1 and 1.7 x 105 cells mL-1. Culture media were fundamental for growth un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been known to mankind since prehistory due to the production of sugar and now it is an important economic crop cultivated in several countries including Pakistan (James, 2008;Figueroa-Rodriguez et al, 2019). Moreover, sugarcane is one of the most important commercial crops that gives essential by products such as sugar, ethanol, molasses, and bagasse (Sipaúba-Tavares et al, 2020). According to the UNFAO, the world's top 10 sugarcane producing countries includes Brazil, India followed by China, Thailand, Pakistan, Mexico, Colombia, Indonesia, Philippines, and United State (Sabiha-Hanim and Halim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known to mankind since prehistory due to the production of sugar and now it is an important economic crop cultivated in several countries including Pakistan (James, 2008;Figueroa-Rodriguez et al, 2019). Moreover, sugarcane is one of the most important commercial crops that gives essential by products such as sugar, ethanol, molasses, and bagasse (Sipaúba-Tavares et al, 2020). According to the UNFAO, the world's top 10 sugarcane producing countries includes Brazil, India followed by China, Thailand, Pakistan, Mexico, Colombia, Indonesia, Philippines, and United State (Sabiha-Hanim and Halim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae grow heterotrophically when they consume organic molecules such as glucose or acetate as their primary source of nutrition [40], and no light is used during cultivation [34]. Additionally, heterotrophic cultivation has received much interest recently as a result of its high cell density and high rate of biomass production [41]. Furthermore, in comparison to photoautotrophic systems, heterotrophic cultivation can achieve more consistent and predictable biomass productivity due to the consistent availability of the energy source in the form of organic carbon uptake [42].…”
Section: Cultivation Of H Lacustrismentioning
confidence: 99%
“…Thus, using a two-stage cultivation method that included perfusion culture during the vegetative stage and stepwise light irradiation during the induction stage, the mixotrophic culture system produced high-density biomass (2.47 g L −1 ), which was 3.09 and 1.67 times greater than batch and fed-batch processes, respectively [42]. Moreover, Sipaúba-Tavaresa et al [41] reported that high cell density increased from 0.4 × 10 5 cells mL −1 to 1.7 × 10 5 cells mL −1 during exponential growth from day 1 to day 10 under mixotrophic cultivation in H. lacustris when using E. crassipes culture medium.…”
Section: Cultivation Of H Lacustrismentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon source is one of the most cost-effective factors in the production of biomasses and pigments [26]. The replacement of basic carbon sources of media (NaHCO3) with cost-effective materials such as glucose and molasses has previously been reported in the cultivation of Spirulina platensis [27][28][29]. Since, there were no published works on the impacts of sugarcane molasses on the cultivation of Arthrospira maxima, the current research was conduct on this area.…”
Section: Introductionmentioning
confidence: 99%